Cervical pedicle screw fixation with the Tianji orthopedic surgical robot - Hao Shen; Jinlong Zhou; Lipeng Yu (Journal of Orthopaedic Surgery and Research)
Abstract Objective To compare the accuracy and safety of implanting cervical pedicle screws (CPS) between orthopedic surgical robot-assisted technique and traditional fluoroscopy-assisted free-hand technique. Methods Retrospective analysis of 95 patients treated with posterior cervical spinal surgery using either Tianji orthopedic surgical robot-assisted or traditional fluoroscopy-assisted free-hand pedicle screw implantation technology from March 2021 to March 2024, including 44 cases in the orthopedic surgical robot group and 51 cases in the traditional fluoroscopy group. Results Compared with the traditional fluoroscopy group, the orthopedic surgical robot group had better accuracy in screw implantation that is, a higher acceptable rate of screws (p = 0.0083). In addition, compared with the traditional fluoroscopy group, postoperative hospital stay was shorter in the orthopedic surgical robot group (p = 0.0447), but operation duration was longer (p = 0.0038). There was no significant difference in intraoperative blood loss between groups (p = 0.0872). There were 2 cases of cerebrospinal fluid leakage and 1 case of decreased left handgrip strength in the traditional fluoroscopy group, while only 1 case of cerebrospinal fluid leakage occurred in the orthopedic surgical robot group. Conclusions In this retrospective study, the accuracy of spine surgery with CPS implantation assisted by orthopedic surgical robot is often superior to that of spine surgery using traditional fluoroscopy-guided CPS implantation technique, while maintaining comparable safety.